REKONSEPTUALISASI MAṬLA‘ DAN URGENSINYA DALAM UNIFIKASI AWAL BULAN QAMARIYAH - Muhaini, Akhmad (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2013)
In Indonesia, frequently occured the differences on initial determination of islamic lunar month such as Ramadhan, Syawal and Zulhijjah. This difference can not be separated from the two major methods of determining begining of lunar month namely á¸¥isÄb (calculation) and ruâ€™yat (observing hilÄl). Apart from debate between á¸¥isÄb and ruâ€™yat, another issue that is also often raises is applicability rukyah and á¸¥isÄb, known as validity of maá¹lÄâ€˜. Meaning of the maá¹lÄâ€˜s concept now seen no longer adequate and unable to overcome that differences. For that reason, reinterpretation of the maá¹lÄâ€˜s meaning is something that is very important. However it should be noted that reinterpretation should not be out of bounds from Shar'i limitation and on the other hand must involve basic science of astronomy so can make it more up to date and more easily accepted rationally.